The Blessings of a Child with Learning Disabilities : An Islamic Perspective - Ibrahim, Nor Hasniah; Saili, Jamayah (2013)
This conceptual paper is aimed to highlight that religious belief can have an important bearing on causal attributions for disability. The birth of a child with a disability may be perceived as ‘God’s will’ and associated with beliefs about Qada (decree) and Qadar (destined), the fifth of the six fundamentals of Iman (faith) among Muslims. The words Qada and Qadar is a very broad concept; it brings the same meaning to some of the metaphorical statements such as: "Things happened for reasons”, “Blessing in disguise”, “Wisdom behind it”, “kun faya kun” (what will be will be). The first section of this paper discusses on the concept of Islamic discourse on impairment and the values that society conveys about disability. This section will elaborate on the life as a testing ground from Islamic perspective. The second part of this article focuses on the practical guidelines in dealing with “trials” of having learning disable children. The guidelines involved four tips in communicating with the child and dealing with special needs children, a God’s gift. The intent is to comprehend some explanations based on the parents experience to the question: “why us?” and set out to understand “what went wrong?”